Viral Inactivation with Emphasis on SARS-CoV-2 Using Physical and Chemical Disinfectants - Abdolmajid Fadaei (Hindawi Limited, 2021)
Background. Recently, an outbreak of a novel human coronavirus SARS-CoV-2 has become a world health concern leading to severe respiratory tract infections in humans. Virus transmission occurs through person-to-person contact, respiratory droplets, and contaminated hands or surfaces. Accordingly, we aim at reviewing the literature on all information available about the persistence of coronaviruses, including human and animal coronaviruses, on inanimate surfaces and inactivation strategies with biocides employed for chemical and physical disinfection. Method. A comprehensive search was systematically conducted in main databases from 1998 to 2020 to identify various viral disinfectants associated with HCoV and methods for control and prevention of this newly emerged virus. Results. The analysis of 62 studies shows that human coronaviruses such as severe acute respiratory syndrome (SARS) coronavirus, Middle East respiratory syndrome (MERS) coronavirus or endemic human coronaviruses (HCoV), canine coronavirus (CCV), transmissible gastroenteritis virus (TGEV), and mouse hepatitis virus (MHV) can be efficiently inactivated by physical and chemical disinfectants at different concentrations (70, 80, 85, and 95%) of 2-propanol (70 and 80%) in less than or equal to 60 s and 0.5% hydrogen peroxide or 0.1% sodium hypochlorite within 1 minute. Additionally, glutaraldehyde (0.5–2%), formaldehyde (0.7–1%), and povidone-iodine (0.1–0.75%) could readily inactivate coronaviruses. Moreover, dry heat at 56°C, ultraviolet light dose of 0.2 to 140 J/cm2, and gamma irradiation could effectively inactivate coronavirus. The WHO recommends the use of 0.1% sodium hypochlorite solution or an ethanol-based disinfectant with an ethanol concentration between 62% and 71%. Conclusion. The results of the present study can help researchers, policymakers, health decision makers, and people perceive and take the correct measures to control and prevent further transmission of COVID-19. Prevention and decontamination will be the main ways to stop the ongoing outbreak of COVID-19.